Erratum: XIN-JUN GAN, HUI-ZHE FENG, HUAN-JIN CHEN, PING-SHENG ZHONG & QIANG FAN (2024) Taxonomic studies on the genus Ophiopogon (Asparagaceae) I:—identity of O. albimarginatus and O. pseudotonkinensis, and a new species O. guangzhouensis from Guangdong, China. Phytotaxa 662 (2): 121–136. - Gan, Xin-Jun; Feng, Hui-Zhe; Chen, Huan-Jin; Zhong, Ping-Sheng; Fan, Qiang (Phytotaxa, 2024)
N/A